2010
DOI: 10.1111/j.1365-2141.2010.08099.x
|View full text |Cite
|
Sign up to set email alerts
|

The management of pregnancy in paroxysmal nocturnal haemoglobinuria on long term eculizumab

Abstract: SummaryIn Paroxysmal nocturnal haemoglobinuria (PNH), pregnancy is associated with increased maternal and foetal complications to such an extent that the condition has been considered relatively contra-indicated in PNH. Eculizumab has revolutionized the treatment of PNH. We evaluate its use in pregnancy to date. We report on seven patients exposed to eculizumab at different stages of pregnancy including the first two patients to receive the drug from conception to delivery. There was no evidence of complement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 15 publications
5
86
0
5
Order By: Relevance
“…35 Importantly, eculizumab seems to be administrable safely in pregnancy in the long term. 36,37 In our study, we found similar C5a levels in healthy pregnant and non-pregnant women and could not detect any association between C5a levels and obstetric parameters, such as fetal birthweight or gestational week at delivery; of note, these pregnancies were without complications.…”
Section: Discussionmentioning
confidence: 54%
“…35 Importantly, eculizumab seems to be administrable safely in pregnancy in the long term. 36,37 In our study, we found similar C5a levels in healthy pregnant and non-pregnant women and could not detect any association between C5a levels and obstetric parameters, such as fetal birthweight or gestational week at delivery; of note, these pregnancies were without complications.…”
Section: Discussionmentioning
confidence: 54%
“…Several recent reports suggest that eculizumab, a humanized monoclonal antibody that binds to the terminal complement protein C5 has the potential to prevent PNH-associated complications in pregnant women receiving anticoagulation therapy and is well tolerated. [29][30][31] However, further, larger studies are required in this setting to confirm these findings. …”
Section: Discussionmentioning
confidence: 57%
“…Nonetheless, preliminary data from HPN patients treated with eculizumab during pregnancy suggest that its use may be safe, at least in the short term, for the fetus (60)(61)(62). In contrast, potential infectious complications may be of concern.…”
Section: Tma In Pregnancy: the Great Paradigm Shiftmentioning
confidence: 99%